Pelatihan Penulisan Karya Ilmiah untuk Guru SMP Ar-Risalah - Zaturrahmi Zaturrahmi; Widya Widya; Yeni Nurpatri; Desy Eka Muliani; Jendriadi Jendriadi; Ena Suma Indrawati; Khairul Ikhwan; Ilham Adi Putra (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
In realizing its vision, SMP Putri Ar-Risalah needs to improve the competence/ability of its teachers. One thing that teachers need to master is the ability to write scientific papers. The ability to write scientific papers needs to be possessed by all teachers. In addition to making it easier for teachers to publish scientific papers, teachers can also motivate students to write diligently. The Adzia University PkM team provided training in writing scientific papers to Ar Risalah Junior High School teachers in the form of material presentations. The purpose of this scientific paper writing training is to improve the teacher's ability to write scientific papers. The result of the evaluation of scientific writing is that the teacher is satisfied with the training provided. According to the teacher, the material presented is up-to-date, effective, useful, and interesting. Teachers are also committed to applying the knowledge and experience gained through this training in carrying out their daily tasks.